“You're listening but you're not hearing”: qualitative exploration of parents' lived experience of paediatric sepsis - O’Keefe, Meagan; Crowe, Liz; Lister, Paula; Schlapbach, Luregn J.; Simons, Megan (Frontiers in Pediatrics, 2025)
BackgroundSepsis is a life-threatening condition of significant mortality and morbidity burden in children. There is limited evidence exploring the lived experiences of parents whose children have survived or died from sepsis, nor their support needs, despite growing awareness of poor sepsis outcomes.ObjectiveThis study aims to understand the lived experiences of parents of children affected by sepsis, both surviving and bereaved, and identify gaps in support services to inform future interventions.MethodsA phenomenological-hermeneutic design was used, with data collected through a focus group and individual interviews with 11 parents of children treated for paediatric sepsis in Queensland, Australia. Reflexive thematic analysis was used to analyse the data.ResultsFour themes were generated that present an in-depth understanding of parents' lived experiences of having a child with sepsis and what their support needs are: 1. Rupture of Life as We Knew It—parents experienced a distinct rupture between life before and after their child's sepsis diagnosis, often accompanied by trauma and grief; 2. Navigating in the Dark—parents described feeling confused and isolated, driven by a lack of awareness about sepsis, inadequate communication from healthcare providers, and limited access to specialised support; 3. The Weight of ‘What If’—guilt, regret and disillusionment with the healthcare system were common among parents, particularly regarding missed early warning signs and opportunities for intervention; and 4. Call for Change—parents advocated for improved public and professional education about paediatric sepsis, trauma-informed communication from healthcare professionals, and the development of structured, specialised support networks.ConclusionParents of children affected by sepsis experience profound distress and isolation, compounded by a lack of awareness, inadequate communication, and limited specialised support services. They identified that urgent action is needed to develop paediatric sepsis-specific family support networks, enhance public and clinical education, and implement trauma-informed care to reduce the burden of sepsis on all families.